Taking scripts as a model of lesson organisation for the integration of culture and language in ELT - Criado Sánchez, Raquel (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2009)
Culture and language are two intertwined constructs essential to understand the interpretation of reality by different communities. Apprehending the foreign language culture is thus vital to attain genuine and fully communicative competence in the L2. This article specifically focuses on the teaching of scripts in ELT. Scripts (Shank and Abelson, 1977) are defined as proceduralised sequences of events of a temporal, cause-and-effect nature which underlie daily stereotyped situations. In this work, scripts are also regarded as cognitive sequences of events for culturally idiosyncratic situations pertaining to a certain linguistic population. The objective of this article is to propose the integration of culture and language teaching in ELT by means of the pedagogical adaptation of scripts for cultural situations made up of an ordered sequence of events. This will be accomplished through the “Communicative Processes-based model of activity sequencing” (CPM). The present proposal attempts at compensating the shortage of traditional culture teaching, which has been almost exclusively restricted to lexis or Elementary Meaning Units (Lado, 1957). The CPM adaptation will be illustrated with a complete ELT lesson created by the author for the script of the Cheese-Rolling festival in the English region of Cotswolds. This lesson will be critically analysed from cultural, pedagogical and cognitive perspectives.